PENELITIAN TINGKAT KEPUASAN MASYARAKAT ATAS PELAYANAN TRANSPORTASI DI KOTA BANDUNG - Dawud1, Joni (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2005)
The research tries to identify citizens? responses with regard to Bandung CityTransportation Engineering Policy to improve the transportation service quality inBandung City. The result shows that the majority of citizens are not quite satisfied with the existing condition.